No pain management for labour: individual and organisational determinants: A secondary analysis of the 2016 French National Perinatal Survey. Issue 6 (June 2022) - Merrer, Jade; Chantry, Anne A.; Blondel, Béatrice; Le Ray, Camille; Bonnet, Marie-Pierre
Abstract : BACKGROUND: Disparities in access to pain management have been identified in several care settings, such as emergency departments and intensive care units, but with regard to labour analgesia, it remains poorly explored. OBJECTIVES: To determine the proportion of women without pain management during labour and its individual and organisational determinants. DESIGN: Secondary analysis of a nationwide cross-sectional population-based study, the 2016 French National Perinatal Survey. SETTINGS: All maternity units in France. PARTICIPANTS: Ten thousand and eleven women who attempted vaginal delivery with a labour duration at least 15 min. MAIN OUTCOME MEASURE: Absence of pain management, defined as absence of any pharmacological or nonpharmacological analgesic method during labour. RESULTS: Among the 10 011 women included, 542 (5.4%) had no labour pain management: 318 (3.7%) of the 8526 women who initially preferred to use neuraxial analgesia and 222 (15.8%) of the 1402 who did not. Using generalised estimating equations stratified according to the maternal antenatal preference for neuraxial analgesia, the common determinants of no labour pain management in both groups were no attendance at childbirth education classes and admission to a delivery unit during the night. Among women who initially preferred to use neuraxial analgesia, those who delivered in units with <1500 annual deliveries compared with units with 2000 to 3499 annual deliveries, were more likely to do without pain management [adjusted odds ratio (OR) = 1.96; 95% confidence interval (CI), 1.39 to 2.78]; among those who did not prefer to use it, women born abroad were more likely to do without labour pain management (adjusted OR = 1.64; 95% CI, 1.12 to 2.40). CONCLUSION: In France, 1 : 20 women had no labour pain management, and this proportion was three times higher among women who preferred not to use neuraxial analgesia. Enhancing maternal information on labour pain and its management, especially nonpharmacological methods, and rethinking care organisation, could improve access to analgesia of any kind.